Sur un Hemiberlesia Ckll. nouveau des montagnes du Caméroun (Homoptera: Coccoidea). - Balachowsky, Alfred Serge (Contributions to Entomology = Beiträge zur Entomologie, 1953)
Nomenclatural Actsmanengoubae Balachowsky, 1953 (Hemiberlesia), spec. n.